Pengaruh Literasi Keuangan dan Lifestyle Terhadap Pengelolaan Keuangan Pribadi Gen-Z pada Mahasiswa IAIN Palopo - Nurul Husna S; Hapid; Samsul Bachri (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
In today's modern era, many people, especially the younger generation, face difficulties in managing their personal finances, which is often caused by low financial literacy and a lifestyle that is not in accordance with financial conditions. This study aims to determine the effect of financial literacy and lifestyle on Gen-Z personal financial management in IAIN Palopo students. the method used in this study uses quantitative methods with multiple linear regression techniques, with a sample size of 75 respondents, namely IAIN Palopo students in the Sharia Economics study program class of 2021, 2022, and 2023. Data collection was carried out using a questionnaire consisting of three variables, namely financial literacy, lifestyle, and personal financial management. The results of this study indicate that financial literacy has a positive and significant effect on student personal financial management, lifestyle has a positive and significant effect on student personal financial management, and simultaneously financial literacy and lifestyle have a positive and sign ificant effect on personal financial management in Gen-Z students of IAIN Palopo.